RATIO DECIDENDI IN DETERMINING TOOLS OF EVIDENCE INSTRUCTIONS FOR SETTLEMENT OF CRIMINAL CASES IN THE MURDER TRIAL - Eddy Wahono; Wahyu Prawesthi (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Evidence is needed to show the truth of the crime that occurred. The importance of evidence as evidence in legal cases greatly influences the outcome of the decision determined by the judge. The completeness and validity of evidence is the most important factor in determining a case decision. So based on the problems above, researchers will conduct an analysis of the application of evidence and obstacles to the application of evidence in Decision Number: 1342 K/Pid/2022. This study uses a normative legal research type with the Statue Approach and Case Approach approaches. Sources of legal material come from the Civil Code (KUHAP) Articles 183 to 189 and Articles 55 and 56 of the Criminal Code. The process of collecting data through a literature study will be analyzed using a qualitative descriptive analysis. The results of this study are: 1) The application of evidence in the court decision Number: 1342 K/Pid/2022 concerning the Criminal Act of Murder is in accordance with the existing requirements and has the force of law in proving the murder case that occurred, and 2) The Judge does not encountered obstacles in the use of evidence to drop Court Decision Number: 1342 K/Pid/2022 concerning the Crime of Murder where evidence was available from the Defendant's Statement, Witness Statement and Physical Evidence that corroborated the occurrence of a violation of the law.